Effect of different forms of rumen-protected fat from palm oil on body weight and sperm quality in Malin sheep - Mohd Hafizal Ahmad (2022)
The study purpose was to evaluate the effect of different forms of rumen-protected fat (RPF) that is high in fatty acid on body weight and sperm quality in male Malin sheep. Twenty male adult Malin sheep were randomly assigned to four treatment groups namely; CON: control, PF: 2% prilled fat, CS: 2% calcium salt fatty acid and CO: 2% canola oil respectively. No significant difference was observed in the body weight changes among the treatment group. Rams that received PF had the highest (P<0.05) semen volume while the animal received CO had the highest (P<0.05) sperm concentration than other treatment group. A significant increase (P<0.05) in the sperm membrane integrity in PF (44%) and CS (42%) than CON. Live sperm was also significantly higher in PF and CS group (79%) than control. No significant effect (P>0.05) was found in abnormal sperm percentage in animals with different dietary supplements with control. In conclusion, the result indicates that supplementation of rumen-protected fat from palm oil to adult male Malin sheep helped to improve the sperm plasma membrane integrity and live sperm.